The Borderline Dysplastic Hip: Arthroscopy or PAO?. Issue 7 (30th July 2018) - Grammatopoulos, George; Pascual-Garrido, Cecilia; Nepple, Jeffrey; Larson, Christopher M.; Bedi, Asheesh; Group, ANCHOR; Beaule, Paul; Clohisy, John C.
Objectives: The borderline dysplastic hip (characterized by a lateral centre-edge angle (LCEA): 20 - 25° and an acetabular index (AI): 10 - 15°) can pose a significant challenge as symptoms may be due to insufficient acetabular coverage, the presence of femoro-acetabular impingement (FAI) or both. Accordingly, different treatment options have been described, including peri-acetabular osteotomy (PAO), hip arthroscopy, open arthrotomy or a combination of procedures. This study aims to determine patient and deformity-specific characteristics that direct treatment decision-making in the borderline dysplastic hip. Furthermore, we describe the early-term results of both the PAO and hip arthroscopy in treating this challenging patient population. Methods: A prospective, multicenter, longitudinal surgical cohort of young adult hips was searched. From 2060 hips, 291 hips satisfied the inclusion criteria of idiopathic borderline dysplasia, adequate follow-up (> 1-year) and functional outcome. Demographic and radiographic features are included in Table 1. Fifty-five hips (19%) had a previous hip operation (most commonly a hip arthroscopy). A number of different procedure types were performed which were broadly divided into 3 groups; PAO-only (n=42), hip arthroscopy-only (n=127) or PAO and intra-articular treatment (either arthroscopically or open, addressing the cam morphology and/or labral pathology) (n=122). Outcome measures included complications-, re-operations- rates and clinical outcomes using the Harris Hip (HHS) and HOOS scores; pre-operatively and at follow-up; the difference was defined as Δ. Patient characteristics, radiographic morphology and clinical outcome measures were compared between the 3 groups. Results: Patients that underwent a PAO were younger and more likely to be female. The PAO groups had a greater number of previous hip procedures (26%, 24%), most of which were hip arthroscopies. The patients that underwent hip arthroscopy had greater incidence of high alpha angles (66%) compared to the PAO groups (35%, 38%) (p<0.001). The PAO groups having slightly more dysplastic features (LCEA, AI, ACEA) (Table 1). At a mean follow-up of 2.5 years, there were no differences in the complication (7-10%, p=0.8) or re-operation rates (13%). Pre-operatively, the PAO groups had inferior HOOS and WOMAC scores compared to the arthroscopy group (p=0.02-7). No differences in the post-op scores were seen (Table 1). The groups that addressed the intra-articular pathology (arthroscopy and PAO-articular treatment) had significantly greater ΔHHS (23) compared to PAO-only (13) (p=0.02). Conclusion: Younger patients, those with a failed previous arthroscopy, without evidence of intra-articular wear and with worse pre-operative function were more likely to receive a PAO (with or without articular adjunct treatment). Addressing the intra-articular and impingement-related pathology (in addition to a when a PAO is considered necessary) was associated with better improvement in PROMs and should be strongly considered in the borderline hip. Table 1. Patient demographics, radiographic parameters, complication-, re-operation rates and patient reported outcome measures for the whole cohort and the three treatment subgroups. Parameter Cohort (n=291) Groups p-value PAO (n=42) Arthrosropy (n=127) PAO& Intro-articular (n422) Age (years old) 27±11 22±7 31±12 24±8 <0.001* Gender (%female) 77% 95% 64% 84% <0.001* BMI 24±4 24±4 24±4 24±4 0.5 Chronicity of pain <1-year 32% 24% 35% 31% 0.04* 1-3years 45% 52% 35% 52% >3 years 13% 24% 30% 17% Previous hip surgery(%) 19% 26% 12% 24% 0.02* Previous arthroscopy(%) 17% 26% 9% 21% 0.1 Acetabular Index/° 9±3 11±3 9±3 10±3 <0.001* LCEA/° 22±2 22±2 23±2 22±2 <0.001* ACEA/° 25±8 23±10 28±6 22±8 <0.001* Cross Over Sign (%) 44% 31% 49% 43% 0.1 Congruity Excellent 31% 59%% 24% 28% <0.001* Good 65% 36% 71% 69% Fair 4% 5% 5% 3% Tõnnis Grade 0 61% 76% 41% 76% <0.001* 1 38% 22% 58% 24% High α Angle (AP or lateral) (%) 50% 36% 66% 38% <0.001* Complication 8% 10% 7% 9% 0.8 Re-operation 18% 19% 16% 20% 0.8 THA by follow-up 2% - 3% - 0.07 HHS_pre-op 60±16 63±19 61±15 58±16 0.07 HOOS_pre-op 54±22 52±21 58±22 50±21 0.02* WOMAC_pre-op 64±22 64±22 67±22 61±22 0.06 SF12_pre-op 37±10 40±10 38±10 35±10 0.03* HHS_post-op 78±19 75±20 80±18 78±19 0.4 HOOS_post-op 77±22 73±23 81±20 75±23 0.07 SF12_Ppost-op 45±12 43±12 47±11 46±12 0.6 ΔHHS 21±25 13±13 23±26 22±20 0.08 ΔHOOS 27±31 20±35 28±31 27±29 0.5 ΔSF12 10±15 4±19 10±16 12±15 0.02*